MARTIN BUBER'S I-THOU RELATIONSHIP: PHILOSOPHICAL FOUNDATIONS AND APPLICATIONS IN THE HUMANIZATION OF HEALTH CARE - Santos, Shirlei da Silva Ferreira Rodrigues; Costa, Cristiane Maria Amorim; dos Santos, Juliano; Spindola, Thelma (Seven Editora, 2024)
This article analyzes the conception of the I-Thou relationship proposed by Martin Buber and its applicability to health care, particularly in nursing. By contrasting the genuine I-Thou encounter with the objectified I-It relationship, it is argued that the Buberian framework can guide more humanized practices, capable of considering not only physical aspects, but also the emotional, spiritual and existential dimensions of the patient. This perspective expands the autonomy, dignity and active participation of the patient in the therapeutic process, in addition to strengthening the ethical responsibility of the professional. Thus, by replacing mere technical execution with an integral and dialogical approach, care becomes an authentic encounter, marked by reciprocity, respect and appreciation of otherness. The article discusses philosophical foundations, spiritual and existential dimensions, as well as practical implications and challenges to incorporate the I-Thou paradigm in health practice, contributing to the construction of a more ethical, comprehensive and humanized care.DOI: https://doi.org/10.56238/sevened2024.037-116